The The influence of social media marketing on brand awareness and brand image: moderating effect of religiosity - Achmad Rifaldo; Yunia Wardi (Marketing Management Studies, 2021)
The purpose of this study was to examine the effect of social media marketing, brand awareness and brand image. In addition, this study also examines the moderating effect of religiosity on the relationship between social media marketing, brand awareness and brand image. The population of this study were followers of HPAI-HNI official social media accounts who are Muslim and domiciled in West Sumatra. This study uses quantitative methods and obtained 253 respondents through an online questionnaire with purposive sampling technique. Data were analyzed using PLS-SEM technique with SmartPLS 3. It was found that social media marketing had a significant positive effect on brand awareness and brand image. In addition, this study found that religiosity was a positive-significant moderating variable on the relationship between social media marketing and brand image but not on brand awareness. This research contributes to the company's branding activities, especially using social media marketing.